IMPLEMENTASI PEMBELAJARAN BERDFERENSIASI DALAM PENDIDIKAN INKLUSI DI SD MUHAMMADIYAH 15 SURABAYA - Nurkholis; Ayu Ghinadi; Jelita Vita Gunawan; Kusila; Rohaeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Inclusive education is an approach in the education system that aims to provide equal learning opportunities for all learners, without exception. In inclusive education, every student, including those with different abilities, backgrounds or individual characteristics, has the same right to receive education in the same school environment as their peers. This concept emphasises the importance of a learning environment that supports the diversity of individual differences in obtaining quality education. SD Muhammadiyah 15 Surabaya has implemented inclusive education through an education unit operational curriculum that involves various parties and integrates local content subjects. This implementation aims to create a friendly and conducive learning atmosphere for all learners without discrimination. In addition, school culture is a major element in supporting inclusive education through programmes such as supporting inclusive education through programmes such as Al-Qur'an tadarus, Cheerful Morning, 5-S, Dhuha prayers, Islamic characteristics, congregational prayers, kultum, and various social and literacy activities. The implementation of this school programme has a positive impact on building discipline, improving academic and non-academic achievements, creating a harmonious environment for all students, and implementing the Pancasila Student Profile (P5). The success of this implementation is inseparable from the support of various stakeholders, including teachers, parents, communities and governments in creating an inclusive and competitive education environment. Keywords: Inclusive education, operational curriculum, flagship programmes, Pancasila Student Profile (P5).